Impacts of Micro- and Nano-Sized Plastic Particles on Benthic Invertebrates: A Literature Review and Gap Analysis - Haegerbaeumer, Arne; Mueller, Marie-Theres; Fueser, Hendrik; Traunspurger, Walter (Frontiers in Environmental Science, 2019)
As documented by the numerous publications that have appeared in recent years, plastic pollution of the environment and the effects on the respective ecosystems are currently one of the most intensely discussed issues in environmental science and in society at large. Of special concern are the effects of micro- and nano-sized plastics. A key issue in understanding the fate and potential effects of micro- and nano-sized plastics is their dynamic nature, as the size, shape, and charge of the particles change over time. Moreover, due to various biological processes, such as the aggregation of organic material and/or bacteria (“biofouling”), the density of plastic particles that settle in the sediments of aquatic ecosystems may be several orders of magnitudes higher than that in the surrounding waters. Consequently, the risk posed by plastic pollution to benthic fauna is considerably high. Nonetheless, the vast majority of studies examining the effects of microplastics have focused on pelagic organisms so far. We therefore conducted a comprehensive literature review to examine the impact of micro- and nano-sized plastics on benthic invertebrates, including the physical and chemical effects of leaching and the interactions of plastic particles with contaminants. Overall, 330 papers were reviewed for their fulfillment of different criteria (e.g., test species, plastic material, particle shape, particle size, exposure concentration, exposure route, assay type, assay duration), with 49 publications finally included in our survey. A comprehensive gap-analysis on the effects of plastic particles on benthic invertebrates revealed a wide variety of effects triggered by micro- and/or nano-sized plastics but also distinct differences regarding the plastic materials tested, the size fractions applied, the shape of the respective particles, and the exposure routes tested. Our review concludes with a discussion of the important research gaps concerning freshwater ecosystems and recommendations for future areas of research.